Holonic Manufacturing System: Current Development and Future Applications - Moses Laksono Singgih (Bandar Lampung University (UBL), 2014)
Holonic Manufacturing Systems (HMS) provides a flexible architecture to the changes and uncertainties of the manufacturing conditions. HMS has developed to meet the needs of consumers who are adapted to the capability of the company.This paper explains holon and holonic manufacturing system, analyzing the needs of the manufacturing system at the upcoming conditions, summarizes the current development of HMS and estimates HMS ability for dealing with the needs of a manufacturing system that will come.